Not Just Another Multicultural Story: The English, From 'Fitting In' to Self-Ethnicisation - Stratton, Jon (University of Queensland Press, 2000)
It would be usual, these days, to argue that the experience of British migrants in Australia is the norm against which the reception of non-British migrants has always been articulated. I will argue that the understanding of how British migrants were expected to experience Australia, and were, and are, experienced by Australians has been ideologically driven, at first, by a need to see the Australian society, and the culture that evolved, as a version of British society and culture and, later, during the era of official multiculturalism, by the desire to assert this culture as the naturalised, core culture of Australia. John Docker writes that the emphasis on Anglo-conformity, which laid the basis for the present-day core culture, became pervasive in the period between the two world wars. Since this period also, and corresponding to the emphasis on Anglo-conformity, there has developed an assumption that migrants from the United Kingdom and Ireland, and, indeed, all English-speaking migrants, would simply 'fit in' to Australian society. By 'fitting in' I do not mean that they would assimilate, assimilation in its classical definition entails the expectation that the person's behaviour and ideas would change to be more congruent with those of the host country. Rather, I mean that there was the assumption, no matter how obviously it was contradicted by actual experiences, that English-speaking migrants would simply merge with the general population. I will argue that such an assumption has continued during the era of official multiculturalism.